Identification of affine term structure models with observed factors: Economic shocks on Brazilian yield curves - Marco Shinobu Matsumura; Ajax Reynaldo Bello Moreira (Institute for Applied Economic Research (ipea), 2015)
We propose different exactly identified specifications of affine models with observed macri factors. The models are compared estimating Brazilian domestic and sovereign yield curves.
Keywords: C13; E43; E52; G12; 330